COMPARISON OF ASTER GDEM IMAGES AND SRTM IMAGES FOR RIVER WATERSHED AND GEOMORPHOLOGY STUDY - Naf’an Arifian; Kemal Rahman Denis; Sri Kandi Putri (Remote Sensing Technology Study Program, 2022)
This study uses two DEM images, namely ASTER GDEM and DEM SRTM to map the distribution of rivers and geomorphology located in The District of Pesisir Selatan. In this study a comparison of the two images was carried out with the same level of resolution of 30 meters to see the accuracy of the images used in the study of watersheds and geomorphology. The method used in this research is processing image data then identifying the river for each image used. Further carrying out a confusion matrix which is used to check or improve data from a quantitative approach. The results of the study in terms of comparison of ASTER and SRTM images for watershed identification show that SRTM imagery is more accurate in identifying watersheds compared to ASTER imagery. After taking samples with the number of sample points taken, namely 36 samples on each, and then testing for spatial accuracy, the results show that the SRTM imagery had an accuracy rate of 88% where out of 36 sample points only 5 were wrong or not on the river. Whereas in the ASTER image of 36 sample points, there were only 6 which were right on the river, show that the level of image accuracy is only 14% for river identification. The study also shows that after the research process and accuracy test, for geomorphologic identification on the two DEM images, namely DEM SRTM and ASTER GDEM, it found that both images have the same level of accuracy, therefore both images are equally good at identifying geomorphology.